TINDAK TUTUR DIREKTIF DAN STRATEGI BERTUTUR GURU BAHASA INDONESIA DI KELAS IX - Laili Etika Rahmawati; Rahmadani Indria Fatikhasari (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The purpose of this study is to describe the form of directive speech acts and describe the Indonesian teacher's speech strategies in class IX at SMP Negeri 3 Colomadu. This study uses a qualitative descriptive method. This research method aims to describe, describe, analyze critically and objectively regarding the forms of directive speech acts and speech strategies of Indonesian teachers in class IX at SMP Negeri 3 Colomadu. The data used in this study are in the form of speech taken from listening to the speech of teachers and students during the teaching and learning process in class. The data collection technique in this study used the Cakap Free Involved Listening technique followed by note-taking and recording techniques. The focus of the research was carried out in order to obtain an overall overview of the forms of directive speech acts and speech strategies of Indonesian language teachers in class IX at SMP Negeri 3 Colomadu. The results of the research that has been done are; first, the dominant directive speech acts used by the teacher in the teaching and learning process in class IX at SMP Negeri 3 Colomadu are speech acts of ordering, begging, suggesting, demanding, and challenging. Second, the speaking strategy used by the teacher in class IX at SMP Negeri 3 Colomadu, namely (1) speaking frankly without preamble, (2) speaking frankly with positive politeness, (3) speaking frankly with politeness. negative, (4) spoke vaguely.